The Influence of E-Wom on Purchase Intention: The Mediating Role of Brand Image And Trust (Study on Consumers of “SME Cosmetic Products”) - Wahyudi, Handri Dian; Sudarmiatin, Sudarmiatin (Cita konsultindo, 2024)
This study investigated the effect of electronic word-of-mouth (e-WOM) on the purchase intentions of potential consumers of SME products, considering the mediating factors of brand image and trust. Convenience sampling technique and explanatory approach were used in the study with 225 participants. Data were analyzed using Partial Least Squares with WarpPLS Software. The results showed that e-WOM has a positive and significant effect on trust, purchase intention and brand image. Brand image also has a positive and significant effect on purchase intention and trust. Trust also has a positive and significant effect on purchase intention. In addition, trust mediates the relationship between product image and purchase intention, brand image between e-WOM and purchase intention, and trust mediates the relationship between e-WOM and purchase intention. The study recommends that SME products improve their brand image, number of positive reviews and trust to increase purchase intentions.